Assessing student perceptions and comprehension of climate change in portuguese higher education institutions - Santos, P. T. (2016)
The higher education system has a critical role to play in educating environmentally aware and participant citizens about global climate change. Yet, few studies have focused on higher education students’ knowledge and attitudes about this issue. This study aims to contribute to a comprehensive understanding of views and attitudes about climate change issues, across the postgraduate student population in three universities—the on Campus University of Porto and University of Coimbra, and the distance learning Universidade Aberta, Portugal. We surveyed university students and graduates from three master programs in environmental sciences targeting their knowledge, attitudes and behaviour on climate change issues, and their views of the role that their master degree had on it. A majority of the respondents believed that climate change is factual, and is largely human-induced; and a majority expressed concerns about climate change. Still, the surveyed students hold some misconceptions about basic causes and consequences of climate change. Further research is necessary to comprehend the university postgraduate students’ population, so that curricula programs can be adapted to grant consensus on scientific knowledge about climate change, and an active engagement of the graduate citizens, as part of the solution for climate change problems.